Structure, function, and evolution of metallo-β-lactamases from the B3 subgroup—emerging targets to combat antibiotic resistance - Krco, Stefan; Davis, Samuel J.; Joshi, Pallav; Wilson, Liam A.; Monteiro Pedroso, Marcelo; Douw, Andrew; Schofield, Christopher J.; Hugenholtz, Philip; Schenk, Gerhard; Morris, Marc T. (Frontiers in Chemistry, 2023)
β-Lactams are the most widely employed antibiotics in clinical settings due to their broad efficacy and low toxicity. However, since their first use in the 1940s, resistance to β-lactams has proliferated to the point where multi-drug resistant organisms are now one of the greatest threats to global human health. Many bacteria use β-lactamases to inactivate this class of antibiotics via hydrolysis. Although nucleophilic serine-β-lactamases have long been clinically important, most broad-spectrum β-lactamases employ one or two metal ions (likely Zn2+) in catalysis. To date, potent and clinically useful inhibitors of these metallo-β-lactamases (MBLs) have not been available, exacerbating their negative impact on healthcare. MBLs are categorised into three subgroups: B1, B2, and B3 MBLs, depending on their sequence similarities, active site structures, interactions with metal ions, and substrate preferences. The majority of MBLs associated with the spread of antibiotic resistance belong to the B1 subgroup. Most characterized B3 MBLs have been discovered in environmental bacteria, but they are increasingly identified in clinical samples. B3-type MBLs display greater diversity in their active sites than other MBLs. Furthermore, at least one of the known B3-type MBLs is inhibited by the serine-β-lactamase inhibitor clavulanic acid, an observation that may promote the design of derivatives active against a broader range of MBLs. In this Mini Review, recent advances in structure-function relationships of B3-type MBLs will be discussed, with a view to inspiring inhibitor development to combat the growing spread of β-lactam resistance.